2016
DOI: 10.5335/rfo.v21i2.6172
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occlusal characteristics of the primary dentition: a cross-sectional study in Brazilian preschool children

Abstract: Objective: The present study aimed to determine the occlusal characteristics and prevalence of malocclusion among Brazilian preschool children. Subjects and method: A cross-sectional study was conducted with 1004 children aged 2-5 years enrolled in public preschools of the city of Canoas, RS, Brazil. A questionnaire was administered to guardians addressing demographic, socioeconomic, and behavioral characteristics of the children and their families. The clinical exam was performed by previously calibrated dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Our results presented no sex differences in either the sagittal relationships of second primary molars and primary canines, or overjet, overbite, crossbite and spacing in accordance with previous studies [ 15 – 17 ]. The present study showed that the majority of the children in the sample (44.8%) had a bilateral ‘flush terminal plane’ molar relationship, an observation consistent with that reported in several other populations [ 1 , 18 , 19 ]. However, much higher percentages have also been reported [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results presented no sex differences in either the sagittal relationships of second primary molars and primary canines, or overjet, overbite, crossbite and spacing in accordance with previous studies [ 15 – 17 ]. The present study showed that the majority of the children in the sample (44.8%) had a bilateral ‘flush terminal plane’ molar relationship, an observation consistent with that reported in several other populations [ 1 , 18 , 19 ]. However, much higher percentages have also been reported [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…52% of children in our study, had a bilateral Class I canine relationship while almost 20% presented asymmetry, in accordance with the studies of Bervian at al [ 1 ] and Abu Alhaija and Qudeimat [ 16 ], in Brazilian and Jordanian schoolchildren respectively. Nevertheless, most previous studies reported higher prevalence of Class I canine relationship at least over 75% [ 4 , 18 , 19 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation